Stress and Damage Analyses of Composite Overwrapped Pressure Vessel. (2015) - Wu, Q.G.; Chen, X.D.; Fan, Z.C.; Nie, D.F.
Abstract: Stress and damage analyses are performed on a composite pressure vessel with aluminum liner under internal pressure through numerical simulations. The variational thickness and wound angle of the head is reflected in the finite element model in accordance with the actual structure. A progressive damage model considering four failure modes are adopted for the composite, i.e., the fiber tension and compression, the matrix tension and compression. The regularities of the initiation and distribution of the various damages are studied, and the effects of the damage evolution on the determinations of the burst pressure and the autofrettage pressure are analyzed. The effects of the autofrettage pressure on the mean stress and the stress amplitude of the liner under zero and service pressures are also discussed. The conclusions in this paper are helpful to the design and use of composite pressure vessels.